Learning Interests with Talking Drawing Strategy of Inclusive Primary School Students in Surakarta - Sari, Erma Kumala (Sebelas Maret University, 2016)
A learning method is necessary in supporting learning activity. Thus, a learning method applied in inclusiveschool should reinforce learning interests and outcomes of students, both normal students and students withÂ special needs. This research aims to determine the effect of Talking Drawing Strategy (TDS) to improveÂ learning interests of the inclusive primary school students in Surakarta. The research applied randomÂ sampling technique with 52 respondents of fourth-class students in two inclusive primary schools inSurakarta. The respondents consist of normal students and students with special needs. Data were gatheredÂ by observations of studentsâ learning interests and a questionnaire about the students learning interest withÂ TDS. Based on descriptive statistical analysis, the research showed that learning activities with TDS canÂ decrease the negative learning behaviours up to 50% in all respondents, 52% in normal respondents, andÂ 45% in respondents with special needs. The research also revealed that (1) 79% of the students like to learnÂ with TDS; (2) 79% of the students stated that TDS is useful in understanding subject matter; and (3) 52% ofÂ the students stated that learning with TDS is easy to do. To sum up, TDS improves the learning interests ofÂ the inclusive primary school students in Surakarta.